Pengaruh Lingkungan Kerja, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan ( Studi Pada Karyawan PT. Jaykay Files Indonesia Semarang ) - Catur Setyaji; Tristiana Rijanti (STIE AMKOP, 2022)
Abstract Human resources play an important role in the organization in improving performance. Robbins and Jugde (2008) state that employee performance is influenced by individuals, groups and the work environment partially affects performance. PT. Jaykay Files Indonesia Semarang is an organization that desperately needs employee performance that can support organizational performance. This study aims to determine the effect of work environment, work discipline, job satisfaction on employee performance at PT. Jaykay Files Indonesia Semarang. The number of respondents who became the sample in this study were 127 employees who were taken based on working age above 5 years. The results of the study were analyzed using multiple linear regression with the help of the SPSS 25 program. The results of the analysis show that: 1) The work environment has a positive and significant effect on employee performance (2) Work discipline has a positive and significant effect on employee performance (3) Job satisfaction has a positive and significant effect on employee performance. Keywords: Work Environment, Work Discipline, Job Satisfaction, and Employee Performance.